2019
DOI: 10.1037/xge0000567
|View full text |Cite
|
Sign up to set email alerts
|

“It feels like it’s in your body”: How children in the United States think about nationality.

Abstract: Concepts of national groups (e.g., Americans, Canadians) are an important source of identity and meaning in people’s lives. Here, we provide a developmental investigation of these concepts. Across 3 studies involving 5- to 8-year-olds and adults in the United States, we found that (a) compared with older children and adults, young children were more likely to think that national groups have a biological basis, but that (b) other aspects of national group concepts—such as the idea that national group membership… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 63 publications
5
41
0
Order By: Relevance
“…In post-accord regions, children's preference for ingroup ethno-national flags points towards an early ethnic conception of nationality, with import placed on their native ethnic symbols. This is consistent with evidence that children may initially conceptualize national category membership as biologically inherited (Davoodi, Soley, Harris & Blake, 2019;Hussak & Cimpian, 2019) and believe that it is not possible to hold more than one civic identity (e.g. Northern Irish and British; Jahoda, 1963a).…”
Section: Ethnic and Civic Conceptions Of Nationalitysupporting
confidence: 84%
See 2 more Smart Citations
“…In post-accord regions, children's preference for ingroup ethno-national flags points towards an early ethnic conception of nationality, with import placed on their native ethnic symbols. This is consistent with evidence that children may initially conceptualize national category membership as biologically inherited (Davoodi, Soley, Harris & Blake, 2019;Hussak & Cimpian, 2019) and believe that it is not possible to hold more than one civic identity (e.g. Northern Irish and British; Jahoda, 1963a).…”
Section: Ethnic and Civic Conceptions Of Nationalitysupporting
confidence: 84%
“…However, more recent work on the development of social cognition demonstrates that even young children hold systemic beliefs about abstract categories, such as nationality (Barrett, 2013;DeJesus, Hwang, Dautel & Kinzler, 2018;Feeney, et al, 2020;Hussak & Cimpian, 2019). Children demonstrate a remarkable ability to detect relevant and salient social information from their surroundings.…”
Section: Children's Ethno-national Flag Categories In Three Divided Societiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies on the development of essentialist beliefs have shown that children think in essentialist terms about many other social categories, including ethnicity, nationality, social class, and religion (e.g., Birnbaum, Deeb, Segall, Ben-Eliyahu, & Diesendruck, 2010;Davoodi, Soley, Harris, & Blake 2020;del Río & Strasser, 2011;Diesendruck & HaLevi, 2006;Hussak & Cimpian, 2019). Further, the degree to which different social categories are essentialized varies depending on the socio-cultural context.…”
Section: Psikoloji çAlışmaları -Studies In Psychologymentioning
confidence: 99%
“…Further, one recent study showed that American children's tendency to essentialize nationality is correlated with their support of global inequalities that favor the U.S. (Hussak & Cimpian, 2019), providing evidence that essentialism might shape children's developing attitudes about social policy. Future research could directly measure the relation between children's tendency to essentialize their national and religious or ethnic groups and their internalization of ethnic or religious nationalist associations.…”
Section: Author Manuscript Development Of Religious Nationalism In Indiamentioning
confidence: 99%